Visual Encounters in the Study of Rural Childhoods - Mitchell, Claudia; Mandrona, April (Book collections on Project MUSE., 2017)
"The modern world is increasingly urban. Yet for the majority of the earth's children (age 0-19), the rural remains a feature of their lives. Even people who have migrated to the cities come from (and bring along) the rural. They travel back to visit family, or they bring their customs into the city with them. Rural life can thus continue to occupy a space in memory and through photographs and other artefacts, even if migration practices and the world of the digital means that tehre are fewer physical and mental traces of it. Visual Encounters and Rural Childhood brings together visual studies and children's studies to look at images of childhood as an entry point to study rurality and rural life. With an impressively global roster of chapter authors and visual culture ranging from film to children's literature to cell phone video, the voices of the children remain central in this investigation into what we can learn about rural life through the media from and about children"--